Accounting System Design for Small and Medium Agriculture Business in West Java - Effendhy, Ibrahim Risyad; Sutardi, Acip (Journal of Innovation, Business and Entrepreneurship, 2016)
Abstract. In the globalization era, SME have to get ready to battle in a tight competition. Based on the statement from Indonesian Ministry of Micro, Small, and Medium Enterprises, Several problems that SME usually faced are human resource, funding, marketing, management and technology, and institutional. Two of five crucial problem for SME that author highlighted management. From the author experience of direct participation with the company, Sangkuriang Situ Mukti deals a lot of time on accounting process. The problem arose since the mid of 2015 when management team could not process its financial data and led to ineffective business process. this paper, Chart Account for Small and Medium Aquaculture Business in West Java Case Study: Sangkuriang Situ Mukti,Â is a part of a whole package of accounting system.